In the footsteps of our ancestors : following homo sapiens into Asia and Oceania - Ueki, Takeshi, 1946-; Summerhayes, Glenn, 1954-; Hiscock, Peter, 1957- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2025)
"In the Footsteps of Our Ancestors details, through archaeological analysis, the dispersal of our species, Homo sapiens, out of Africa and into Asia and Oceania. This book provides a comprehensive picture of early human migration and provides crucial information to our understanding of the global story of human evolution and cultural diversification. Chapters from an international team of experts provide the necessary geographical and temporal coverage for this ambitious book. Controversies around timing and pathways and competing models are explored in an area where archaeological data can be scarce. Genetic and archaeological data often seem inconsistent but this book uses the latest developments in archaeological science to maximise the amount of information from genetic data. This cutting-edge analysis is used to help plot the pattern of migration or migrations that lead to the contemporary cosmopolitan distribution of our species. In the absence of up-to-date treatments, this book provides the only comprehensive coverage of this important topic and is a major scientific contribution to archaeology and evolutionary anthropology that will help shape the direction of future research for years to come. In the Footsteps of Our Ancestors is an essential text for researchers and students of archaeology, anthropology and human evolution"--
Beginnings : Africa and beyond / Peter Hiscock, and Kim Sterelny -- The colonisation of South Asian homo sapiens : assessing alternative hypotheses through cladistic analyses of lithic assemblages / Chris Clarkson, Ravi Korisettar, Ceri Shipton, Mark Collard, Briggs Buchannan -- The settlement of mainland Southeast Asia by anatomically modern humans / Charles Higham -- A middle to late Upper Pleistocene lithic industry from north Vietnam / A.P. Derevianko and A.V. Kandyba -- Early modern humans in island Southeast Asia / Daud Tanudirjo -- Northern Sahul and the Bismarck Archipelago / Glenn R. Summerhayes -- Human dispersals across southern and central Sahul / Peter Hiscock and Kim Sterelny -- The peopling of East Asia : perspectives from the Russian Far East / A.V. Tabarev -- Early peopling in and around Taiwan : Pleistocene through Middle Holocene groups before the Austronesian era / Hsiao-chun Hung, Chin-yung Chao, Hirofumi Matsumura, and Mike T. Carson -- The arrival of modern humans in north China during the late Palaeolithic / Xing Gao and Li Feng -- The Philippines : origins to the end of the Pleistocene / Alfred Pawlik and Philip Piper -- Emergence of Pleistocene modernity and its background in the Korean Peninsula / Yongwook Yoo -- Analyzing Japanese sites belonging to the initial period of the Upper Palaeolithic : creating macro-models / Takeshi Ueki -- Archaeological materials from the Japanese early Upper Palaeolithic and their implications / Takuya Yamaoka -- Pleistocene Okinawa : unique culture and lifeway in the Oceanic islands of the Western Pacific / Masaki Fujita -- Appendix A. Comparision of radiocarbon and calibrated dates / Yuichiro Kudo -- Appendix B: Analyzing the age and heating history of archaeological materials using remnant magnetization / Hideo Sakai.
Keywords: Prehistoric peoples -- Asia; Prehistoric peoples -- Oceania; Paleolithic period -- Asia; Paleolithic period -- Oceania; Human beings -- Migrations